Targeting ataxia telangiectasia mutated and Rad3 related kinase (ATR) in PTEN deficient breast cancers for personalized therapy - Al-Subhi, Nouf; Ali, Reem; Abdel-Fatah, Tarek; Moseley, Paul M.; Chan, Stephen Y.T.; Green, Andrew R.; Ellis, Ian O.; Rakha, Emad; Madhusudan, Srinivasan (Springer, 2018)
Purpose: PTEN, a negative regulator of PI3K signaling, is involved in DNA repair. ATR is a key sensor of DNA damage and replication stress. We evaluated whether ATR signaling has clinical significance and could be targeted by synthetic lethality in PTEN deficient triple negative breast cancer (TNBC). Methods: PTEN, ATR and pCHK1Ser345 protein level was evaluated in 1650 human breast cancers. ATR blockade by VE-821 was investigated in PTEN-proficient (MDAMB-231) and PTEN-deficient (BT-549, MDA-MB-468) TNBC cell lines. Functional studies included DNA repair expression profiling, MTS cell-proliferation assay, FACS (cell cycle progression & γH2AX accumulation) and FITC-annexin V flow cytometry analysis. Results: Low nuclear PTEN was associated with higher grade, pleomorphism, dedifferentiation, higher mitotic index, larger tumour size, ER negativity, and shorter survival (p values <0.05). In tumours with low nuclear PTEN, high ATR and/or high pCHK1ser345 level was also linked to higher grade, larger tumour size and poor survival (all p values <0.05). VE-821 was selectively toxic in PTEN deficient TNBC cells and resulted in accumulation of double strand DNA breaks, cell cycle arrest, and increased apoptosis. Conclusion: ATR signalling adversely impact survival in PTEN deficient breast cancers. ATR inhibition is synthetically lethal in PTEN deficient TNBC cells.